Siberian Confessional Identity of Late 19th - Early 20th Centuries: Factor of Palestinian Pilgrimage - V. A. Gerasimova (Научный диалог)
The phenomenon of Russian religious identity in Siberia is considered. Religious and secular texts of Siberian authors of 19th - early 20th centuries, documents of regional archives are used as a material. Special place is given to the issues of “religiosity” and special “mores of Siberians.” The aim is to analyze the process of actualization of traditional conservative Russian values in Siberia. The author concludes that the transformation of the regional Siberian identity was influenced by the concept of “Russian Palestine.” It was one of the unique “repositories” of national cultural memory and Russian identity. The intervention of the Russian tradition in Palestine was carried out for centuries, as a result of which a unique religious and cultural phenomenon arose thousands of kilometers from the borders of Russia. Despite the changes and upheavals within the country, “Russian Palestine” retained its functions as a “repository,” became a kind of intertemporal field on which the formation, verification and consolidation of new, specific religious and cultural ideas and values took place, through the Holy land the connection of Siberia with Central Russia occurred. The main communication bridge between Siberia and the Holy land were Siberian Orthodox pilgrims. The main purpose of the pilgrimage, according to the Siberian clergy, was to raise the religious feelings of believers, “the improvement of the Orthodox faith.” The way to Palestine for the Siberian Gentiles who converted to Christianity was the way to acquire Russian identity.